Some Thoughts on Rebuilding African State Capability - A. Peter Mutharika (Washington University Law Quarterly, 1998)
Communism has collapsed, the United States is now the only superpower, and modem information technology has created a global neighborhood. As American capital and technology seek foreign markets, the viability of the world's second largest continent should be of at least some interest to the American lawyer. I want to talk about what the World Bank in its 1997 World Development Report has called a "Crisis of Statehood-A Crisis of Capability" in Sub-Saharan Africa in particular and in Africa in general and how the African States in cooperation with the international community might respond to it.
Keywords: Foreign investments -- Africa; Economic development -- Africa; Africa -- Commerce; State (Political science)